Pengaruh Kualitas Layanan Dan Promosi Terhadap Loyalitas Konsumen Melalui Kepuasan Sebagai Variabel Intervening (Studi Kasus Pada Pengguna Jasa Penerbangan Sriwijaya Air Di Bandar Udara Kalimarau Berau Kalimantan Timur) - Oktavia Yuniar; M Hufron; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
AbstractThis study aims to analyze the direct effect of service quality and promotion variables on satisfaction, the direct effect of service quality and promotion on customer loyalty, the direct effect of satisfaction on customer loyalty, and the indirect effect of service quality and promotion variables on customer loyalty through satisfaction. The population of this research is the users of Sriwijaya Air flight services at Kalimarau Berau Airport in East Kalimantan. Sampling was conducted using the Maholtra method so that there were 85 respondents who met the requirements as a sample. This research was conducted by distributing questionnaires and path analysis methods. The results of this study indicate that the variables of service quality and promotion have a direct effect on satisfaction, service quality and promotion have a direct effect on customer loyalty, satisfaction has a direct effect on customer loyalty, service quality and promotion have an indirect effect on consumer loyalty through satisfaction as an intervening variable.Keywords: service quality, promotion, customer loyalty, satisfaction.